Subchondral insufficiency fractures: overview of MRI findings from hip to ankle joint - Buturoiu, Monica Maria; Ghiea, Sorin; Weber, Marc-André (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2024)
Subchondral insufficiency fracture (SIF) represents a potentially severe condition that can advance to osteoarthritis, with collapse of the articular surface. SIF manifests as a fracture in bone weakened by non-tumorous disease, precipitated by repetitive physiological stress, without a clear history of major trauma. It is observed along the central weight-bearing region of the femoral condyle, with a higher incidence in the medial femoral condyle, but also in other large weight-bearing synovial joints, such as the femoral head, tibial plateau, or talus.A review of the literature from the past six years was performed by searching PubMed and ScienceDirect databases, using the keywords “subchondral insufficiency fracture” and “spontaneous osteonecrosis of the knee”. The inclusion criteria were scientific papers presented in the English language that reported on the magnetic resonance imaging (MRI) aspects of SIF of the lower limb.Detecting SIF at the level of the hip, knee, and ankle may present challenges both clinically and radiologically. The MRI appearance is dominated by a bone marrow edema-like signal and subchondral bone changes that can sometimes be subtle. Subchondral abnormalities are more specific than the pattern of bone marrow edema-like signal and are best shown on T2-weighted and proton-density-weighted MR images. MRI plays an important role in accurately depicting even subtle subchondral fractures at the onset of the disease and proves valuable in follow-up, prognosis, and the differentiation of SIF from other conditions.
Keywords: Subchondral insufficiency fracture; Hip; Knee; ankle; Magnetic resonance imaging